Genome-wide polymorphism and genic selection in feral and domesticated lineages of Cannabis sativa - Patrick Woods; Nicholas Price; Paul Matthews; John K McKay (G3: Genes, Genomes, Genetics, 2022)

(untitled)
AbstractA comprehensive understanding of the degree to which genomic variation is maintained by selection vs. drift and gene flow is lacking in many important species such as Cannabis sativaC. sativaFST